Doğmakta olan Avrupa gazeteciliği kavramı - Karadağ, Gökmen H. (My University, 2005)
50 yılın üzerinde bir geçmişe sahip fiili Avrupa bütünleşme süreci, geleceğine dair belirsizliklere rağmen işlemekte ve birçok alanı olduğu gibi işitsel-görsel sektörü, gazetecilik pratiklerini de etkilemektedir. Yeni Avrupa'ya paralel olarak yeni bir Avrupa gazeteciliğinden söz edilmektedir. Bu çalışmada AB oluşum süreci paralelinde Avrupa çapında işitsel-görsel alanda ve gazetecilik pratiklerinde ne gibi değişiklikler olduğuna bakılmaktadır. Avrupa Birliği'nde demokratik açık, kamusal alan açığı ve kimlikteki açık olarak ifade edilen üçlü açığın küçültülmesinde medyaya, gazetecilere dolaylı ya da doğrudan biçilen roller bu çalışmada eleştirel bir şekilde sorgulanmıştır. Yeni Avrupa Gazeteciliği adına şimdilik sadece olgunlaşmamış formlardan söz edilebilir. AB haberciliğinin çok önemli bir uzmanlık dalı olarak algılanması ve doğru gazetecilik adına bu konudaki uzmanlaşmanın geliştirilmesi gerekmektedir ama gazetecinin geleneksel niteliklerinin üstünde, AB ilintili bir misyonla donatılmış bir Avrupa Gazeteciliği formuna, gazetecilik ile halkla ilişkiler ya da basın sözcülüğü arasındaki önemli ve hassas ayrım açısından dikkatle ve eleştirel bakmak gerekmektedir. John Keane'nin belirttiği üzere 20. Yüzyıl'ın sonunda tüm küreselleşmeye rağmen demokrasi hala çok savunmasız konumdadır ve medyaya bu anlamda önemli bir iş düşmektedir. AB oluşumu da - çok sıradışı olsa da - bir anlamda bir küresel girişimdir ve demokrasi, insan hakları adına tüm risklerden arınmış değildir. Yeni Avrupa Gazeteciliği'nde gazeteciliğin geleneksel soruşturmacı ve eleştirel yanının AB bütünleşmesi gündeminin gölgesinde kalması kamusal alanın eleştirel işlevini zayıflatacaktır. EMERGING CONCEPT OF EUROPEAN JOURNALISM Gökmen H. Karadağ

The actual European integration process, which is older than 50 years, is still rolling in spite of uncertainities, and as such it affects several fields as it does the audio-visual sector and journalism practices. There is a talk of a New European Journalism in parallel to the new Europe. In this study, changes that occur across Europe in the audio-visual field and journalism practices during the formation process of the EU are examined. The media's and journalists' directly or indirectly ascribed responsibilities regarding the reduction of the three-fold European deficit which comprises the democratic deficit in the European Union, public sphere deficit and identity deficit, have been critically investigated in this study. In the name of the New European Journalism one can only talk of immature forms. EU reporting should be considered as a very important expertise on its own and this should be developed for the sake of right journalism. However, beyond a journalist's traditional qualities, a European Journalism form associated with any EU-related mission should be carefully and critically investigated in terms of the deliberate distinction between journalism and public relations or press spokesmanship. As John Keane already stated, democracy is still considerably defenseless in spite of the globalization in the 20th century, and therefore this incurs significant responsibilities to the media. The EU formation is -even if quite an extra ordinary one- a global endeavour, and democracy and human rights are not free of all risks. Within the framework of the New European Journalism, a possible overshadowing of the traditional investigative and critical dimension of journalism by the EU integration agenda would only weaken the criticizing function of the public sphere. ABSTRACT The actual European integration process, which is older than 50 years, is still rolling in spite of uncertainities, and as such it affects several fields as it does the audio-visual sector and journalism practices. There is a talk of a New European Journalism in parallel to the new Europe. In this study, changes that occur across Europe in the audio-visual field and journalism practices during the formation process of the EU are examined. The media's and journalists' directly or indirectly ascribed responsibilities regarding the reduction of the three-fold European deficit which comprises the democratic deficit in the European Union, public sphere deficit and identity deficit, have been critically investigated in this study. In the name of the New European Journalism one can only talk of immature forms. EU reporting should be considered as a very important expertise on its own and this should be developed for the sake of right journalism. However, beyond a journalist's traditional qualities, a European Journalism form associated with any EU-related mission should be carefully and critically investigated in terms of the deliberate distinction between journalism and public relations or press spokesmanship. As John Keane already stated, democracy is still considerably defenseless in spite of the globalization in the 20th century, and therefore this incurs significant responsibilities to the media. The EU formation is -even if quite an extra ordinary one- a global endeavour, and democracy and human rights are not free of all risks. Within the framework of the New European Journalism, a possible overshadowing of the traditional investigative and critical dimension of journalism by the EU integration agenda would only weaken the criticizing function of the public sphere.
Keywords: Gazetecilik; Gazetecilik ve gazeteleri tarihi ve kişilere göre ele alış; Gazetecilik ve yayıncılık; Genel Konular